2019
DOI: 10.1186/s12917-019-1892-y
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ultrasound, computed tomography and computed tomography arthrography of the cranial cruciate ligament, menisci and cranial meniscotibial ligaments in 10 radiographically normal canine cadaver stifles

Abstract: Background Bilateral non-traumatic cranial cruciate disease is frequently seen in originally unilateral cruciate pathology. Untreated cranial cruciate ligament disease and concurrent meniscal lesions cause progressive osteoarthritis and pain of the stifle joint. Early presurgical diagnosis is important, but remains difficult. The purpose of this ex vivo study was (1) to describe the ultrasonographic appearance of the canine cranial cruciate ligament (CrCrL), menisci and meniscal ligam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(93 reference statements)
1
8
0
1
Order By: Relevance
“…Of the study population, 25% underwent bilateral TPLO, consistent with previous studies that reported a range of 17 to 61%. 1,2,7 The signalment of our study population was consistent with other studies on cranial cruciate ligament disease and medial meniscal tears. 2,13,23 Sex and neuter status were not identified as risk factors for bilateral meniscal tears in this study; however, breed and age were significant.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Of the study population, 25% underwent bilateral TPLO, consistent with previous studies that reported a range of 17 to 61%. 1,2,7 The signalment of our study population was consistent with other studies on cranial cruciate ligament disease and medial meniscal tears. 2,13,23 Sex and neuter status were not identified as risk factors for bilateral meniscal tears in this study; however, breed and age were significant.…”
Section: Discussionsupporting
confidence: 90%
“…1 Bilateral cranial cruciate ligament rupture, identified during single or staged surgeries, shows a reported occurrence of 17 to 54%. 1,2,6,7 The menisci contribute to joint stabilization by aiding in shock absorption, load transmission, prevention of synovial membrane impingement between the femur and tibia, joint proprioception and joint lubrication. [2][3][4][8][9][10] In full extension, the menisci transmit $50 to 70% of the body weight, which increases to 85 to 90% in flexion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetische resonantie (MR) is een uitstekende niet-invasieve beeldvormingstechniek voor het diagnosticeren van subtiele letsels van de menisci bij de hond (Martig et al, 2006;Böttcher et al, 2010;Przeworski et al, 2016;Franklin et al, 2017;Van der Vekens et al, 2019). De gevoeligheid en specificiteit van MR voor de diagnose van mediale meniscusletsels zijn respectievelijk 68% (of 75%, afhankelijk van de referentiestandaard) en 100% (Franklin et al, 2017).…”
Section: Magnetische Resonantie (Mr)unclassified